Struktur Kepemilikan Terhadap Pengungkapan Akuntansi Sumber Daya Manusia - Nova Maulud Widodo; Ari Kuncara Widagdo (Universitas Merdeka Madiun, 2020)
Abstract— This study aims to analyze and test the ownership structure influence on the human resource accounting disclosure (HRAD). This study empirically examine the influence of ownership structure that is foreign ownership and family ownership on the HRAD. Control variables on this study are firm SIZE, CAR, LDR, and AGE. This study used secondary data obtained through the Indonesia Stock Exchange. HRAD is measured using an index Mamun. The sample was banking companies listed on the Indonesian Stock Exchange 2011-2014 period selected through purposive sampling method. Total annual reports used for analysis were 133 reports. Methods of data analysis in the study using multiple linear regression with SPSS software. The structure of ownership in this study by considering authenticity. In this study, foreign ownership and family ownership is measured by two measurements. The measurement foreign ownership results showed no influence on the HRAD. Family ownership using the first measurement has no influence on HRAD, while using the second measurement significant negative influence. Control variables in this study is the company SIZE and AGE and have positive influence on the HRAD. While the CAR and LDR have negative inluence on the HRAD. Keywords—: human resource accounting disclosure; ownership structure; banking company.